Migrating to Opportunity : Overcoming Barriers to Labor Mobility in Southeast Asia - Testaverde, Mauro; Moroz, Harry; Hollweg, Claire H.; Schmillen, Achim (Washington, DC: World Bank, 2017)
The movement of people in Southeast Asia is an issue of increasing importance. Countries of the Association of Southeast Asian Nations (ASEAN) are now the origin of 8 percent of the world's migrants. These countries host only 4 percent of the world's migrants but intra-regional migration has turned Malaysia, Singapore, and Thailand into regional migration hubs that are home to 6.5 million ASEAN migrants. However, significant international and domestic labor mobility costs limit the ability of workers to change firms, sectors, and geographies in ASEAN.